La diversificación del riesgo en la cartera de créditos del sector financiero con base en la teoría de portafolios (2019)
The present article provides the results from the application of a credit portfolio theory developed by Markowitz in 1956 to a test group made up of 3011 companies from the real sector, classified by economic activity and by size. This study shows that in our environment it is possible to use the principle of diversification in order to reduce risk in credit portfolios, by assigning corporate credits between sectors sharing few correlations. This reduction in risk implies a lowering in the capital necessary for provisions for non performing loans, in accordance with the Basel Accord and its effects on the Raroc (Risk Adjusted Return on Capital.) The article demonstrates how to be in accordance with one of the criteria that drew most attention in the Accord, namely the segmentation of portfolios, now that the level of correlation between the different sectors is definitely an important factor in controlling the risk in a credit portfolio, as it is in designing portfolios with minimum risk.